Openness in the NHS: a secondary longitudinal analysis of national staff and patient surveys - Imelda McCarthy; Jeremy Dawson; Graham Martin (BMC, 2020)
Abstract Background Improving openness-including candour when things go wrong, and willingness to learn from mistakes-is increasingly seen as a priority in many healthcare systems. This study explores perceptions of openness in England before and after the publication of the Francis report (2013), which examined failings of openness at one English hospital. We examine whether staff and patients' views on openness, and experiences of giving voice to concerns, have changed since the report's publication for better or worse. Methods Organisational-level data was collated for all trusts from the NHS National Staff Survey (2007-2017), NHS Acute Inpatient Survey (2004-2016) and NHS Community Mental Health Service User Survey (2007-2017). Survey items related to openness were identified and longitudinal statistical analysis conducted (piecewise growth curve and interrupted latent growth curve analysis) to determine whether there was evidence of a shift in the rate or direction of change following publication of the Francis report. Results For some variables there was a discernible change in trajectory after the publication of the Francis report. Staff survey variables continued to rise after 2013, with a statistically significant increase in rate for "fairness and effectiveness of incident reporting procedures" (from + 0.02 to + 0.06 per year; p < .001). For the patient surveys, the picture was more mixed: patient views about information provided by accident and emergency staff rose from a 0.3% increase per year before 2013 to 0.8% per year afterwards (p < .01), and inpatients being involved in decision making increased from a 0.4% rise per year before 2013 to 0.8% per year afterwards (p < .01); however, there were not rises in the other questions. Mental health patients reported a decrease after 2013 in being listened to (decreasing at a rate of 1.9% per year, p < .001). Conclusions Data suggest that the Francis inquiry may have had a positive impact on staff and acute inpatients' perceptions and experiences of openness in the NHS. However such improvements have not transpired in mental health. How best to create an environment in which patients can discuss their care and raise concerns openly in mental health settings may require further consideration.